‘When Faith Is Not Enough’: Encounters between African Indigenous Religious Practices and Prophetic Pentecostal Movements in Zimbabwe - Molly Manyonganise (Religions, 2024)
African Pentecostalism remains the fastest growing form of Christianity on the African continent. Scholarship on Zimbabwean Pentecostalism has noted how the emergence of New Pentecostal Movements (NPMs), specifically Prophetic Pentecostalism (PP), has increased this growth. Apart from other attracting factors, such as the Holy Spirit, claims of faith healing, deliverance and prophecy, among others, African Pentecostalism is known for its emphasis on faith as a major anchor of any Pentecostal Christian. Hebrews 11, with its emphasis on faith, is, therefore, a central scripture in this Christian tradition. However, the emergence of NPMs at the height of the Zimbabwean crisis from the year 2008 to the present, has challenged Zimbabwean Pentecostal Christians from their sole dependency on faith. The crisis called for much more than faith could stand on its own. Hence, NPMs responded to this need by infusing indigenous religious practices with biblical ones as a way of strengthening believers through the crisis. Prophetic Pentecostal Movements (PPMs) in Zimbabwe introduced touchable objects such as anointed towels, handkerchiefs, wrist bands, stickers, oils and even condoms. While this appears to be sophisticated syncretism, a critical analysis of the practices shows how steeped they are in the African indigenous religious worldview. This article, therefore, seeks to examine the religious encounters between indigenous African religious practices and Pentecostal practices as practiced in the NPMs in Zimbabwe. The focus of this paper is to establish the resilience of indigenous religious practices within a Christian tradition that claims to have totally broken from the past. It further argues that the fast growth of PPMs depends on the ‘Christianization’ of indigenous religious practices, which are presented to believers as ‘purely biblical’. This is largely a desktop research project in which secondary sources were used as sources of data.